Decision Support System Evaluasi Tingkat Keberhasilan UMKM Menggunakan Weighted Scoring Method - Mochammad Darip; Sigit Auliana; Prio Kustanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving regional economic growth, yet most business owners still face challenges in objectively evaluating their business conditions. The assessment process, which relies heavily on experience and intuition, often results in business decisions not being supported by measurable information. This study aims to develop a web-based Decision Support System (DSS) to evaluate the success rate of MSMEs using the Weighted Scoring Method. The study employed a Research and Development (R&D) approach, encompassing needs analysis, system design, method implementation, and application testing. The evaluation process involved six key indicators, weighted according to their importance, then calculated to produce a final score, classified into three success levels: high, medium, and low. The results showed that the system was able to automate the evaluation process, consistently display success rate classifications, and generate reports in PDF format to document the assessment results. Testing using real MSME data demonstrated that the system's calculations were consistent with manual calculations based on the applied method. The developed system is expected to assist MSMEs in conducting more systematic business evaluations and support local governments in the development and data-driven decision-making process.